2022
DOI: 10.1097/spv.0000000000001258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Vibegron for the Treatment of Overactive Bladder in Women: A Subgroup Analysis From the Double-Blind, Randomized, Controlled EMPOWUR Trial

Abstract: Importance The international phase 3 EMPOWUR trial demonstrated efficacy and safety of vibegron, a newer b 3 -adrenergic receptor agonist, in adults with overactive bladder (OAB). Women are disproportionately affected by OAB, especially those with bothersome symptoms, such as urge urinary incontinence (UUI). Objective This subgroup analysis from EMPOWUR assessed efficacy and safety of vibegron in women. Study Design In EMPOWUR, patients with OAB were randomized 5:5:4 to 12 weeks of treatment with once-daily vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A recent systematic review by Yeowell et al 8 found that treatment with mirabegron was associated with greater adherence and longer time to discontinuation compared with anticholinergics with use of ER formulations also noted to be associated with greater adherence. Given the more recent U.S. Food and Drug Administration approval for vibegron, data regarding continuation rates are limited; however, these likely mirror those of mirabegron given its documented tolerability 21,22 . In this context, the finding that beta-agonists are associated with the worst coverage is concerning as it creates a significant obstacle to initiation and continued use of an effective and safe medication therapy for OAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review by Yeowell et al 8 found that treatment with mirabegron was associated with greater adherence and longer time to discontinuation compared with anticholinergics with use of ER formulations also noted to be associated with greater adherence. Given the more recent U.S. Food and Drug Administration approval for vibegron, data regarding continuation rates are limited; however, these likely mirror those of mirabegron given its documented tolerability 21,22 . In this context, the finding that beta-agonists are associated with the worst coverage is concerning as it creates a significant obstacle to initiation and continued use of an effective and safe medication therapy for OAB.…”
Section: Discussionmentioning
confidence: 99%
“…Given the more recent U.S. Food and Drug Administration approval for vibegron, data regarding continuation rates are limited; however, these likely mirror those of mirabegron given its documented tolerability. 21,22 In this context, the finding that beta-agonists are associated with the worst coverage is concerning as it creates a significant obstacle to initiation and continued use of an effective and safe medication therapy for OAB. This lack of coverage for preferred medications combined with existing insurance policies requiring medication trials before moving on to alternative therapies result in an increased unnecessary exposure to anticholinergics and cognitive harm.…”
Section: Discussionmentioning
confidence: 99%
“…The body of evidence supporting the use of antimuscarinic medications and beta-3 (b3) adrenergic agonist oral medications has demonstrated improvement in urgency urinary episodes, voiding episodes, and UUI [8][9][10][11][12][13][14][15][16][17] as compared to placebo. Clinical studies have also demonstrated that OAB agents significantly improve other outcomes of interest, including overall and condition-specific QoL, 10,11,14,[18][19][20] satisfaction with treatment, 9 and work productivity 21 ; however, there is considerable variance in estimated magnitudes of effects, [8][9][10][11][12][13][14][15][16] and given the lack of evidence indicating superiority for either class when evaluating OAB symptoms control, the Panel concluded that the efficacies of antimuscarinic medications and b3-agonists were similar. Furthermore, the Panel felt it was important to note that the observed placebo effect is very strong in some clinical studies.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Most clinical studies included assessments of efficacy and/or side-effects at 4 weeks and most were able to demonstrate medication effects by that time. [10][11][12][13]16 Assessment after initiating OAB therapy is important to avoid medical "purgatory," in which patients remain in a state of none to minimal improvement or significant side-effects. Those who do not achieve appropriate improvement should be offered change in therapy.…”
Section: (Clinical Principle)mentioning
confidence: 99%
See 1 more Smart Citation